Penerapan Integrated Project Delivery untuk Mewujudkan Ruang Operasi yang Nyaman dan Sehat - Muhammad Luthfan Nur Azmi; Ahmad Saifudin Mutaqi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
This research analyzes the implementation of Integrated Project Delivery (IPD) methodology in hospital operating room construction to create a work environment that supports optimal health and comfort standards. The research method uses a qualitative approach by combining systematic literature review and case study analysis at JIH Purwokerto Hospital. Data analysis process was conducted through cross-verification techniques with thematic coding to identify effectiveness patterns of IPD implementation. Research results indicate that IPD implementation can optimize air ventilation systems through HVAC technology integration with H13-H14 HEPA filter standards, creating environmental parameter stability that supports medical activities. Strategic synergy between IPD and Building Information Modeling (BIM) produces effective cross-disciplinary coordination, eliminating communication barriers among project stakeholders. Implementation of Internet of Things (IoT) technology within the IPD framework provides significant contributions to medical data management efficiency and real-time operational environment quality monitoring. Economic aspect evaluation shows construction cost efficiency reaching 30% with substantial change order reduction. Despite facing contractual challenges in the Indonesian context, IPD implementation successfully creates a reference model for optimizing healthcare facility development with international standards.